Family structure, education and women's employment in rural India - Sowmya Dhanaraj; Vidya Mahambare (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper investigates if residing in a joint family affects non-farm employment for married women in rural India. Our estimates based on a longitudinal survey of over 27000 women conducted in 2005 and 2012, and using the conditional logistic regression and instrumental variable approach suggest that living in a joint family lowers married women's non-farm employment by more than 10 percentage points. The adverse impact is higher for younger women, for women from families with higher social status, and for those residing in Northern India. We present evidence to suggest that women with higher education levels are not constrained from cultural and traditional norms that lower women's decision-making power and mobility in a joint family. An increased education level is likely to raise women's earning capacity as well as the quality of jobs which may help in lowering family pressure against work. The results suggest that public policies that encourage higher education, improving job accessibility along with affordable childcare, especially for women with less education will raise non-farm employment for women living in a joint family.
Keywords: J21; J22; J12; 330; non-farm employment; family structure; female autonomy; rural areas